2015
DOI: 10.1021/acs.iecr.5b00534
|View full text |Cite
|
Sign up to set email alerts
|

Selective Extraction of Metals from Chloride Solutions with the Tetraoctylphosphonium Oleate Ionic Liquid

Abstract: The solvent extraction behaviour of a series of metal ions (Li + ,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 56 publications
2
57
1
1
Order By: Relevance
“…Sodium oleatew as added in slight excessa nd should also be removed during washing with water.T he total organic carbon (TOC) values in the final washing water were 28 [oleate],r espectively.T his is similar to the water contentso fc omparable water-saturated ILs in the literature. [27] The resulting ILs wereanalyzed by using 1 [25] and the integralsw ere in agreement with the theoretical valuest ow ithin the accuracy of the method. Thus, [N 8888 ][oleate] was synthesized successfully.F or [P 666,14 ][oleate],h owever,t he integrals were slightly off;f or example, the CH 3 protons (d = 0.90 ppm) should con-tribute1 5H and the CH 2 protons of the second peak (d = 1.31 ppm) should account for 52 H. This indicatest hat there might have been as lighte xcess of (sodium) oleate presenti n the IL that was not washed out.…”
Section: Il Synthesismentioning
confidence: 79%
See 2 more Smart Citations
“…Sodium oleatew as added in slight excessa nd should also be removed during washing with water.T he total organic carbon (TOC) values in the final washing water were 28 [oleate],r espectively.T his is similar to the water contentso fc omparable water-saturated ILs in the literature. [27] The resulting ILs wereanalyzed by using 1 [25] and the integralsw ere in agreement with the theoretical valuest ow ithin the accuracy of the method. Thus, [N 8888 ][oleate] was synthesized successfully.F or [P 666,14 ][oleate],h owever,t he integrals were slightly off;f or example, the CH 3 protons (d = 0.90 ppm) should con-tribute1 5H and the CH 2 protons of the second peak (d = 1.31 ppm) should account for 52 H. This indicatest hat there might have been as lighte xcess of (sodium) oleate presenti n the IL that was not washed out.…”
Section: Il Synthesismentioning
confidence: 79%
“…Commonly,t his type of IL is synthesizedi no rganic solvents, such as toluene and ethanol. [25,26] The potentialt oxic effects of remaining trace amounts of synthesis solvent may be observed when these traces leak into the water phase in whichm icroorganisms are present.T op revent possible toxic effects, ao nepot synthesis protocol for the ILs was followedw ith only water as the solvent, similart ot hat described by Parmentier et al [27] To decrease the potential toxicity of the ILs, an organic and biodegradable anion was selected, that is, oleate. [28] The N 8888 cation was demonstrated to be less viscous than asymmetrical ammonium branched cations.…”
Section: Il Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…As reported in the literature such mechanism is based on ion-pair extraction. 25,41,42 Before using the IL, it was pre-saturated with water to decrease the viscosity and to facilitate electrospraying. The aqueous metal salt solution was prepared by dissolving 0. the experiments was synthesized using the same method as previously described and had a purity of…”
Section: Experiments and Materials Materialsmentioning
confidence: 99%
“…This is in agreement with previous research, in which it was already observed that the IL, [N 8888 ][C18:1], showed good extraction for Co and Mn, but low extraction for Ca and no extraction for Na when physical mixing is applied. 25,41 Applying EHDA resulted in an improvement of the selectivity towards the valuable transition metals. The separation factor of Co over Ca and Mn over Ca was respectively, 3.68 and 3.69 when applying physical mixing while during electrospraying at 5 kV a separation factor of respectively 5.00 and 4.84 was observed.…”
Section: / 14mentioning
confidence: 99%